Solving stress clashes in the music of the Cantigas de Santa Maria - Massini-Cagliari, Gladis [UNESP] (2021)
This work aims to investigate how the stress clashes, or the sequences of two or more stressed syllables, can be solved, in terms of prominence relationship (strong/weak), considering the first ten Cantigas de Santa Maria, attributed to Alfonso X (1221-1284). The objective is to search for clues in the music that can reveal which of the syllables in sequence had prominence, in the established rhythmic relationship. It is an analysis in the Phonology field, which aims to examine the possible contributions of observing the musical structure of the cantigas which accompany the verses, written in the Portuguese ancient medieval ancestral language, to determinate the linguistic prosody of that specific period of the language. Observing the length and the prominence of the notes relating to the syllables involved in the stress clash, the analysis shows that the apparent stress clashes in the lyrics of the cantigas were resolved in their musical performance.